2019
DOI: 10.1111/nyas.14119
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of the interscapular brown adipose tissue in mouse

Abstract: The recent discovery of significant brown fat depots in adult humans has revived discussion of exploiting brown fat thermogenesis in the control of energy balance and body weight. The sympathetic nervous system (SNS) has a key role in the activation of brown fat and functional mapping of its components will be crucial for the development of specific neuromodulation techniques. The mouse is an important species used for molecular genetic modulations, but its small size is not ideal for anatomical dissections, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 53 publications
4
40
1
Order By: Relevance
“…Next, we looked for evidence of PRV labeling in DRG sensory neurons. In a similar study of interscapular brown adipose tissue-derived PRV labeling, we identified a low, but consistent PRV labeling in the DRG (Francois et al, 2019). In contrast to interscapular brown adipose tissue (iBAT)-related labeling (Francois et al, 2019;Münzberg et al, 2019), DRG ganglia showed only occasional PRV labeling with typically <5 neurons per ganglion and most often observed in DRG T11 and T12 in 46 and 30%, respectively, of all analyzed animals ( Figure 3, Table 2).…”
Section: Microscopy and Image Processingsupporting
confidence: 65%
See 2 more Smart Citations
“…Next, we looked for evidence of PRV labeling in DRG sensory neurons. In a similar study of interscapular brown adipose tissue-derived PRV labeling, we identified a low, but consistent PRV labeling in the DRG (Francois et al, 2019). In contrast to interscapular brown adipose tissue (iBAT)-related labeling (Francois et al, 2019;Münzberg et al, 2019), DRG ganglia showed only occasional PRV labeling with typically <5 neurons per ganglion and most often observed in DRG T11 and T12 in 46 and 30%, respectively, of all analyzed animals ( Figure 3, Table 2).…”
Section: Microscopy and Image Processingsupporting
confidence: 65%
“…In a similar study of interscapular brown adipose tissue-derived PRV labeling, we identified a low, but consistent PRV labeling in the DRG (Francois et al, 2019). In contrast to interscapular brown adipose tissue (iBAT)-related labeling (Francois et al, 2019;Münzberg et al, 2019), DRG ganglia showed only occasional PRV labeling with typically <5 neurons per ganglion and most often observed in DRG T11 and T12 in 46 and 30%, respectively, of all analyzed animals ( Figure 3, Table 2). We note that iWAT-derived PRV was not co-localized with TH-positive DRG neurons which lack authentic catecholaminergic functions (Kummer, Gibbins, Stefan, & Kapoor, 1990).…”
Section: Microscopy and Image Processingsupporting
confidence: 65%
See 1 more Smart Citation
“…Adaptive thermogenesis by BAT is triggered by release of NE from postganglionic sympathetic neurons (69), and NE levels in BAT under steady-state conditions have historically been used as a direct index of SNS innervation of BAT (70). We did not observe any signi cant effects of DDT or DDE on NE or DHPG levels in BAT from 4-month old female mice.…”
Section: Discussionmentioning
confidence: 99%
“…BAT nerves were later comprehensively investigated by the Bartness research group [3]. Energy expending BAT was the first adipose tissue to be identified as being highly innervated due to its important role in thermogenesis [4], which requires significant sympathetic nervous system (SNS) input and release of norepinephrine [2, 5, 6]. Sensory innervation has also been documented in BAT, particularly around vasculature, and has been proposed to play a role in lipolysis [7].…”
Section: Introductionmentioning
confidence: 99%